Country-level association between antimicrobial consumption and resistance in Neisseria meningitidis: An ecological study - Sheeba S. Manoharan-Basil; Natalia Gonzalez; Chris Kenyon (Elsevier, 2022)
Background: It is unclear what is responsible for the large variations in the prevalence of meningococcal resistance to cephalosporins and quinolones. Methods: We used mixed-effects linear regression to assess if country-level prevalence of reduced susceptibility to cefotaxime and ciprofloxacin was associated with the population-level consumption of cephalosporins and quinolones in 13 European countries. Results: Positive correlations were found between the prevalence of reduced susceptibility to ciprofloxacin and the consumption of quinolones (coef. 0.16, 95% CI 0.05-0.27; P = 0.003). The same positive association was found for cefotaxime/cephalosporins (coef. 0.1, 95% CI 0.04-0.15; P = 0.001). Conclusions: Meningococcal reduced susceptibility to cefotaxime and ciprofloxacin is linked to homologous class antimicrobial consumption. This finding provides additional motivation for strengthening antimicrobial stewardship programs.